Lundu District Council (LDC) / Normaizan Zambri - Normaizan, Zambri (University Technology MARA Sarawak, 2011)
Lundu District Council (LDC) is one of the Local Authority which is known as Local AuthorityLundu District after its establishment on 1 January 1953 under the Local Authority Ordinance 1948.LDC is located at Lundu town where it is a central to the business and administrative activities which takes about 78 km from Kuching. LDC has fifty seven employees which the higher position is the Secretariat N41. Sir Francis Liew Shong Lee. This organization had created seven division or units on their structure organization in order to perform their functions in their core services. LDC played a significant role in performs the duties of management and administration in Lundu District and Sematan District under the Ministry of Environment and Public Health, State of Sarawak. Besides that also, LDC are fully responsible in providing local authorities and socio- economic development of rural and urban communities in the Lundu area which include infrastructure, public health, beautification or landscaping, library services and development that is planned for conveniences ofthe people in the administration ofthe council. Committed in providing a quality services to the customer is the most focuses of this organization. In order to perform a variety of services, carrying out the functions of planning, organizing, controlling and implementing the development and use the resources with effective and efficient in the area of administration, LDC has set the directions of their organization through the formulation of their Vision, Mission, Objectives, Quality Policy, Strategy and Customer Charter. (Source: Application for the establishment of positions based on contributions in LDC year 2010)